A β-glucuronidase-responsive albumin-binding prodrug programmed for the double release of monomethyl auristatin E. Issue 12 (15th November 2018) - Renoux, Brigitte; Fangous, Laure; Hötten, Camille; Péraudeau, Elodie; Eddhif, Balkis; Poinot, Pauline; Clarhaut, Jonathan; Papot, Sébastien
Abstract : Synthesis, in vitro and in vivo biological evaluations of a β-glucuronidase-responsive albumin-binding prodrug bearing a chemical amplifier. Abstract : We report on the synthesis, in vitro and in vivo biological evaluations of a dimeric β-glucuronidase-responsive albumin-binding prodrug designed for the double release of MMAE upon a single enzymatic activation step. This prodrug produced a significant antitumour activity in mice bearing subcutaneous LS174T colorectal adenocarcinoma xenografts without inducing side effects.